The Effect of Technology In Mathematics Learning: Peran Teknologi dalam Pembelajaran Matematika - Pagau, Dwi Alfidya; Mytra, Prima (Universitas Cokroaminoto Palopo, 2023)
This study aims to describe the role of technology in the implementation of mathematics learning. This writing is based on a literature review of journal articles. It is concluded that the use of technology in learning mathematics has a positive impact. Technology can be used as a source of student learning. Technology can visualize abstract mathematical objects into concrete objects that are easily accessible to students. There are various platforms that support the learning process without time limits and various applications that can be used as a learning space for the teacher's role. However, it is undeniable that technology can have a bad effect on students, for example technology provides easy information for students in terms of instant answers available on the internet and even the use of technology can reduce algebraic abilities. Minimizing this impact requires the ability of HOTS in the implementation of mathematics learning and changing the views of teachers and students towards technology, making technology a partner in learning mathematics. The use of technology with the right use can have a better impact on learning mathematics.